Organic osmolyte betaine mitigates the deleterious effects of Diclofenac in vivo in wistar albino rats - Mohd Basheeruddin; V. Lavanya; Neesar Ahmed; Shazia Jamal (Universidade de São Paulo, 2023)
Abstract Diclofenac sodium (DF) is a non-steroidal anti-inflammatory drug (NSAID) that possesses antipyretic, analgesic, antinociceptive and anti-inflammatory activities. Like other NSAIDs, DF is known to be associated with renal, cardiovascular, and gastrointestinal complications. The present study was carried out to evaluate the adverse effects of DF in vivo in wistar albino rats and to assess if oral administration of the organic osmolyte betaine mitigates the adverse effect of DF. Eighteen male Wistar rats were divided into three groups, one group of animals was fed orally with 20 mg/kg of DF once/day, and the other group received a combination of 20 mg/kg of DF and 30 mg/kg of betaine, once/day. Apart from the hematological and biochemical parameters, histopathological changes in the liver, lungs, brain, heart and kidney were also investigated. Histopathological alterations that were found in the liver, kidney, and lungs of DF-treated animals were found to be minimal or absent in DF + betaine-treated animals, as compared to untreated control. The results showed that betaine mitigates the adverse effects associated with DF treatment.